Acquisition premiums and the recognition of identifiable intangible assets in business combinations pre- and post-IFRS adoption. Issue 2 (2nd July 2018) - Su, Wun Hong; Wells, Peter
Abstract : Purpose: This paper aims to evaluate the relation between acquisition premiums and amounts recognised as identifiable intangible assets (IIAs) in business combination, in periods before and after transition to International Financial Reporting Standards (IFRS). Design/methodology/approach: This is an empirical archival research using data from business acquisitions. Findings: In the pre-IFRS period, there is evidence of firms recognising IIAs in business combinations having higher acquisition premiums. This association of acquisition premiums and IIAs ceased with transition to IFRS, notwithstanding the relative latitude provided in accounting standards for the recognition of IIAs. Research limitations/implications: This paper complements the study by Su and Wells (2015) which founds little association between IIAs and performance subsequent to business acquisitions prior to transition to IFRS. The results here suggest that it is attributable to overpayment. Problematically, the incentives for opportunism remain and an issue requiring address is whether alternative sources of accounting flexibility in relation to business combinations exist, such as goodwill which is no longer subject to mandatory amortisation. Practical implications: The results are consistent with accounting opportunism and suggest "overpayment" and accounting flexibility having an economic consequence. This would be expected to result in asset impairments in subsequent periods; however, there is little evidence of this occurring. Social implications: These results have relevance for regulators concerned with the operation of regulation relating to business acquisitions (AASB 3) and intangible assets (AASB 138). Originality/value: This paper complements a number of papers concerned with the recognition of IIAs in business combinations and confirms what many researchers in the area typically assume (triangulation).